The awareness level of orthodontic treatment among early adolescents (a survey among students of 111 public Junior High School, Jakarta) - Khuzaima Adyasti; Dwita Pratiwi; Erwin Siregar (DiscoverSys Inc., 2021)
Objective: The purpose of this study is to describe the distribution of the awareness level of orthodontic treatment in students of 111 Public Junior High School, Jakarta and to compare it between male and female subjects.Material and Methods: A cross-sectional study was held to 107 students aged 12-14 years old in 111 Public Junior High School, Jakarta. This study was analyzed using univariate and Mann-Whitney analysis with a 95% confidence level.Results: The awareness level of most students is moderate (45.8%), followed by high level of awareness (33.6%) and low level of awareness (20.6%). The median and range of the total score in female subjects are 28 (14-34), while in male subjects, the median and range are 24 (13-34). There is significant difference of orthodontic treatment awareness between male and female subjects (P = 0.028).Conclusion: The awareness level of orthodontic treatment in early adolescents is moderate. Female subjects have higher level of awareness about orthodontic treatment than male subjects.